Apoptotic cell death in disease—Current understanding of the NCCD 2023 - Vitale, Ilio; Pietrocola, Federico; Guilbaud, Emma; Aaronson, Stuart A.; Abrams, John M.; Adam, Dieter; Agostini, Massimiliano; Agostinis, Patrizia; Alnemri, Emad S.; Altucci, Lucia; Amelio, Ivano; Andrews, David W.; et al. (Cell Death and Differentiation, 2023)
Apoptosis is a form of regulated cell death (RCD) that involves proteases of the caspase family. Pharmacological and genetic strategies that experimentally inhibit or delay apoptosis in mammalian systems have elucidated the key contribution of this process not only to (post-)embryonic development and adult tissue homeostasis, but also to the etiology of multiple human disorders. Consistent with this notion, while defects in the molecular machinery for apoptotic cell death impair organismal development and promote oncogenesis, the unwarranted activation of apoptosis promotes cell loss and tissue damage in the context of various neurological, cardiovascular, renal, hepatic, infectious, neoplastic and inflammatory conditions. Here, the Nomenclature Committee on Cell Death (NCCD) gathered to critically summarize an abundant pre-clinical literature mechanistically linking the core apoptotic apparatus to organismal homeostasis in the context of disease.
CRIS-Team Scopus Importer:2023-05-05